2002
DOI: 10.1096/fj.01-0533com
|View full text |Cite
|
Sign up to set email alerts
|

Absence of inducible nitric oxide synthase modulates early reperfusion‐induced NF‐κB and AP‐1 activation and enhances myocardial damage

Abstract: The role of nitric oxide (NO) generated by the inducible NO synthase (iNOS) during myocardial ischemia and reperfusion is not understood. We investigated the role of iNOS during early reperfusion damage induced in genetically deficient iNOS (iNOS-/-) mice and wild-type littermates. In wild-type mice, ischemia (60 min) and reperfusion (60 min) induced an elevation in serum levels of creatine phosphokinase and myocardial injury characterized by the presence of scattered apoptotic myocytes and mild neutrophil inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 63 publications
9
79
1
Order By: Relevance
“…We also reported that the overexpression of HSP-25 protein in renal epithelial LLC-PK1 cells using adenoviral vectors protects cells from injury due to oxidants and chemical anoxia (6). HSPs suppress cytokine-induced IL-8 and TNF-␣ expression and the translocation of the p65 subunit of NF-B, which regulates iNOS expression (13,55). In iNOS Ϫ/Ϫ mice, however, where the preconditioning effect is mitigated, the expression of HSP-25 is elevated in both iNOS Ϫ/Ϫ and iNOS ϩ/ϩ animals.…”
Section: Effect Of Fifteen Minutes Of Ischemic Preconditioning On Posmentioning
confidence: 88%
“…We also reported that the overexpression of HSP-25 protein in renal epithelial LLC-PK1 cells using adenoviral vectors protects cells from injury due to oxidants and chemical anoxia (6). HSPs suppress cytokine-induced IL-8 and TNF-␣ expression and the translocation of the p65 subunit of NF-B, which regulates iNOS expression (13,55). In iNOS Ϫ/Ϫ mice, however, where the preconditioning effect is mitigated, the expression of HSP-25 is elevated in both iNOS Ϫ/Ϫ and iNOS ϩ/ϩ animals.…”
Section: Effect Of Fifteen Minutes Of Ischemic Preconditioning On Posmentioning
confidence: 88%
“…Recently, many investigators have documented the role of eNOS 10,37 or iNOS 18,38,39 in the cardioprotective effect of IP. Our data suggest that in the case of I-R injury after IP, activated eNOS produced from recruited EPCs plays an essential role in cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented a favorable role of iNOS in IP. 18,38,39 In particular, Wang et al 40 reported that IP upregulated iNOS in cardiomyocytes and played a protective role against myocardial damage. These authors showed iNOS mRNA expression in ischemic myocardium followed IP, and diffuse iNOS signals were detected with in situ hybridization and immunohistochemistry in the cytoplasmic space of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mRNA expression of TGF-β in isoproterenolinfused iNOS knockout mice was increased more than 10 times suggesting that a deficiency of iNOS may make subjects more vulnerable to isoproterenol-induced heart failure. Sustained increases of IL-6 and TGF-β in iNOS knockout mice may be caused by modulation of signal transduction mediated by nuclear factor-κB or/and activator protein 1 in iNOS knockout mice (Zingarelli et al, 2002). Cytokines expression such as TNF-α and IL-6 in the heart following ischemia and reperfusion damage was more augmented in iNOS knockout mice than wild-type mice (Zingarelli et al, 2002).…”
Section: Discussionmentioning
confidence: 97%